Emotional Responses of Corrective Feedback in Teacher Training Class at University Level - J Ari Wibowo (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2018)
Considering and comprehending the right way of student in learning are requirement to become an effective language teacher. Long (1991) essentially claims that the building block of learning a second language can be found in negotiation for meaning, or the interaction, reformulation, and feedback that occur when people try to communicate. This study present the findings of research carried out to collect data of learner’s emotional respond to oral corrective feedback process.In this research, the researcher uses both qualitative and quantitative approach. It is qualitatively describe the emotional respond of the students to the teacher’s Corrective Feedbacks on their performances in microteaching class at University of Nusantara PGRI Kediri by collecting the data based on planning and conducting skill of an instruction. The data base comprises questionnaire of students’ emotional respond of the feedback in the naturalistic classroom situation. The quantitatively analysis of the data showed that more than half of the corrective feedback made by the teacher is appreciated and needed by the students. However, consistency would become a crucial point for them. It is, thus, recommended that this line of enquiry be followed-up by other researcher so that teachers, teacher trainers and policy makers